Self-perception of oral health among tertiary-care users: quanti-qualitative analysis with chronic kidney disease patients - Amaral, Marcelo Augusto; Miotto, Aline Maria Malachini; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (Universidade Estadual de Maringa, 2022)
Chronic kidney disease (CKD) has become a global public health challenge. The objective of this study was to analyze the relationship between self-perception of oral health and clinical condition among patients with CKD. This is a quanti-qualitative survey conducted in a CKD specialized service. The sample consisted of 60 patients who underwent oral examinations to have their severity of caries (DMFT) and need for dental prosthesis checked. Age, sex, time on dialysis, marital status, skin color, education and pre-existing diseases were also analyzed. Among the kidney patients who agreed to undergo the clinical examinations and showed communication skills, some were selected, and three focus groups were created, with the participation of a moderator and six to 10 kidney patients in each group. Their speeches were processed in the IRAMUTEQ software and analyzed through the similarity analysis and word cloud techniques. As for profile, the patients were aged 60.23 ± 10.87 years old; were male (73.33%); were on dialysis for 41.90 ± 56.57 months; were married (61.67%); were white (76.67%); had incomplete primary education (41.66%); had arterial hypertension (76.67%); had a DMFT index of 22.55 ± 8.39; 43.33% needed an upper complete denture; and 30.00% needed a lower complete denture. The similarity analysis revealed many doubts and uncertainties about current health services, which can be proven by the words ‘no’ and ‘treatment’. The quanti-qualitative analysis showed a high rate of dental loss and the need for complete dentures and suggests inequities in oral health care for chronic kidney disease patients, especially in tertiary care. There was a positive representation regarding oral health, but the lexicographical analyses of the textual corpus confirmed the self-perception of lack of dental care.
Keywords: oral health; qualitative research; renal insufficiency, chronic